Theme-based cause-effect planning for multiple-scene story generation - Ang, Karen S. (Animo Repository, 2011)
Early literacy in children begins through picture drawing and the subsequent sharing of an orally narrated story out of the drawn picture. This is the basis for the Picture Books story generation system whose motivation is to produce a textual counterpart of the input picture in order for the child to associate words with images. However, stories are comprised of sequences of events that occur in a cause-effect loop, and the singlescene input picture approach may lead to a story whose event flow may not match the child's original intended story. In this paper, we present Picture Books 2, which provides an environment for a child to creatively define a sequence of scenes for his input picture and then uses a theme-based cause-effect planner to generate a fable story narrating the flow of events across the scenes for children age 6-8 years old.